Firm heterogeneity in productivity across Europe: evidence from multilevel models. Issue 1 (2nd January 2016) - Aiello, Francesco; Ricotta, Fernanda
Abstract : This paper analyses the Total Factor Productivity (TFP) heterogeneity of a sample of manufacturing firms operating in seven EU countries (Austria, France, Germany, Hungary, Italy, Spain and the UK). TFP data refer to 2008. The empirical setting is based on the multilevel modeling which provides two main results. Firstly, we show that TFP heterogeneity is largely due to firm-specific features (85% of TFP variability in the empty model). Interestingly, we find that some key-drivers of firm performance (size, family management, group membership, innovations and human capital) are significantly related to TFP, but do not, on the whole, absorb much of firm TFP variance, implying that differences in productivity are due to notable yet unobservable firm characteristics. Secondly, as far the role of localization is concerned, we demonstrate that the country effect is more influential than region effect in explaining individual productivity. Net of the country effect, the localization in different European regions explains about 5% of TFP firm heterogeneity. When considering the case of three individual countries, France, Italy and Spain, location in different regions explains 5.3% of TFP heterogeneity in Italy, while this proportion is lower (3.6%) in France and higher (9.9%) in Spain.